Pemberdayaan Masyarakat Desa Tambong Melalui Inovasi Produk Wisata Unggulan Batik Watu Rejeng Dalam Upaya Akselerasi Desa Wisata di Kabupaten Banyuwangi - Eka Afrida Ermawati; Aprilia Divi Yustita; Esa Riandy Cardias (Indonesian Journal Publisher, 2025)
Batik is one of Indonesia's cultural heritages that we must preserve. Almost all regions in Indonesia have their own distinctive batik motifs that are different from each other. Currently, there are around 5,849 batik motifs in Indonesia spread from Aceh to Papua. Banyuwangi, as a destination that has various types of tourism, has twelve typical batik motifs that represent Banyuwangi culture itself. The variety of batik motifs in Banyuwangi has motivated Tambong Village to have batik with motifs that can represent their region and also be something to buy for visitors who travel to the area. However, this desire is hampered by the lack of a distinctive motif. To overcome this problem, this community service activity provides a solution that is expected to be able to solve partner problems. One of the solutions is the creation of a batik motif that is able to represent Tambong village as one of the Ijen Geoparks, named Batik Watu Rejeng.